Effects of oral administration of an aqueous ginger extract on anxiety behavior and tryptophan and serotonin metabolism in the rat - Bano, Samina; Sharif, Humaira; Badawy, Abdulla A-B (Asian Journal of Medical Sciences, 2021)
Background: Zingiber officinale (ginger) is used widely as a herb and medicine. It contains among its constituents 6-Gingerol (a phenol) and quercetin (a flavonoid) that possess anxiolytic and antidepressant properties, but the potential biochemical mechanism(s) of these effects has not been assessed, particularly in relation to serotonin synthesis and neurotransmission. Aims and Objectives: We investigated the anxiolytic-like activity of an aqueous ginger extract by evaluating its influence on behavior, and its effects on serotonin metabolism and on metabolism and disposition of the serotonin precursor tryptophan (Trp) in rats. Materials and Methods: An aqueous ginger extract was given orally in a single daily dose equivalent to 500 mg of ginger material per kg body weight for 3 weeks. The elevated plus maze test of anxiety and Trp metabolism and disposition and brain serotonin synthesis and turnover were assessed in Ginger-treated and control rats. Results: When compared with controls, ginger-treated rats showed a significant increase in the time spent in the open arm, indicative of decreased anxiety. However there was no effect on locomotor activity in open field test. The extract caused significant decreases in activities of liver Trp 2,3-dioxygenase and significant increases in concentrations of serum Trp and corticosterone and brain Trp, serotonin and the major serotonin metabolite 5-hydroxyindoleacetic acid. Conclusion: An aqueous ginger extract exerts an anxiolytic effect in a behavioral model of anxiety, which may be caused by increased serotonin synthesis, and influences tryptophan metabolism and disposition in a manner analogous to antidepressant drugs.